ANALYSIS OF COMMUNITY PERCEPTIONS ON THE DISTRIBUTION OF MARINE WASTE ON THE WEST ACEH COAST - isbah, faliqul; lisdayanti, eka; najmi, nurul; marlian, neneng (JURNAL PERIKANAN TROPIS, 2024)
This research aims to evaluate the effectiveness of waste prevention efforts that have been carried out by the community in Johan Pahlawan District and Bubon District. Through qualitative and quantitative research methods, data was collected from field surveys, interviews, and statistical analysis regarding waste management practices, community participation, and levels of environmental awareness. The results of the research show that the community in both sub-districts has implemented waste prevention efforts well. An increase in environmental awareness among the community can be seen from active participation in waste management activities, waste separation, and the use of environmentally friendly products. Implementation of policies by local governments also makes a positive contribution in creating a cleaner and more sustainable environment.This research provides a comprehensive picture of waste prevention practices that have been successfully implemented by the community in Johan Pahlawan and Bubon Districts. It is hoped that these findings will provide insight for the government and related institutions to increase the sustainability of waste prevention efforts at the local level and stimulate similar practices in other areas.